2021
DOI: 10.1177/16878140211030152
|View full text |Cite
|
Sign up to set email alerts
|

Cattaneo–Christov theory for a time-dependent magnetohydrodynamic Maxwell fluid flow through a stretching cylinder

Abstract: This research work explores the thermal and mass transport phenomena for a time-dependent Maxwell fluid flow in the presence of Cattaneo–Christov concept. The Maxwell fluid flow is analyzed through a stretching cylinder and sheet. Brownian motion, non-uniform heat source/sink, thermophoresis, and variable thermal conductivity are operated in this study. A theoretical analysis of the modeled system of equations is explored with the help of HAM. Impacts of fixed constraints on velocity, thermal, and concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The temperature of the cylinder surface and ambient fluid is assumed to be T w and T c respectively, where T w < T c . The magnetic field of intensity H, is generated by a magnetic dipole located below the sheet at steady distance c. Under the above assumptions the idea of [34] is explored and the continuity, momentum and energy equations in cylindrical coordinates take the following form: Under the above assumptions the idea of [34] is explored and the continuity, momentum and energy equations in cylindrical coordinates take the following form:…”
Section: Mathematical Flow Equations With Flow Geometrymentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature of the cylinder surface and ambient fluid is assumed to be T w and T c respectively, where T w < T c . The magnetic field of intensity H, is generated by a magnetic dipole located below the sheet at steady distance c. Under the above assumptions the idea of [34] is explored and the continuity, momentum and energy equations in cylindrical coordinates take the following form: Under the above assumptions the idea of [34] is explored and the continuity, momentum and energy equations in cylindrical coordinates take the following form:…”
Section: Mathematical Flow Equations With Flow Geometrymentioning
confidence: 99%
“…The governing set of equations, i.e., momentum, energy equations are converted into a set of ordinary differential equations using the following similarity transformation with the help of [34]:…”
Section: Transformation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…They advised that the opposite behavior shows near the surface for curvature parameter, also temperature increase at a distance from the cylinder. MHD Maxwell fluid flow above a stretching cylinder is considered by 10 and concluded that the heat and concentration distribution vary for rising non-Newtonian parameters values.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Christov [7] developed the model of Cattaneo, which is called the Cattaneo-Christov heat flux model. Numerous research works were conducted to analyze the impacts of Cattaneo-Christov heat flux [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%